Dynamic nozzles for drop generators - Castrejón-Pita, JR; Willis, S; Castrejón-Pita, A (2015)
In this paper, a novel mechanism allowing greater control over the formation of droplets is presented. This is achieved via the use of a dynamic nozzle of adjustable diameter. It is demonstrated that, by using such a nozzle, it is possible to greatly modify the formation and breakup of the ligament behind the main drop, leading to an overall reduction in the number of satellite droplets. Furthermore, by adjusting the delay between the beginning of the forming of the drop and the start of the nozzle constriction, a greater control over both the number of satellites and the size of the main drop can be achieved. It is also shown that only a minimal reduction of the nozzle's effective diameter is required in order to exploit the positive effects of the technique presented here. This opens the possibility of incorporating the technique into current droplet generator systems, e.g., via the use of piezoelectric driven nozzles or other micro-mechanical actuation technology.